Ninth Five Year Plan of Kerala 1997-2002 Mid Term Appraisal - Planning Commission (Planning Commission, 1999)
The perspective for the State’s Ninth Plan envisages a growth rate in State Domestic Product of 7 per cent per annum. To achieve this, the total investment contemplated was of the order of Rs.52000 crores. In this, the State sector outlay is fixed at Rs. 16100 crores, balance anticipated from Central Government, Public sector undertakings and Private sector. Out of the State sector outlay of Rs. 16100 crores, the likely Plan expenditure in the first three years is Rs.9240 crores in nominal terms.
State Planning Board Thiruvananthapuram Government of Kerala